Pediatric Hypovitaminosis D - Rafiu Ariganjoye MD, MBA, FAAP, FAIHQ, CPE, CHCQM (SAGE Publishing, 2017)
Vitamin D, a secosteroid, is essential for the development and maintenance of healthy bone in both the adult and pediatric populations. Low level of 25-hydroxy vitamin D (25-(OH)-D) is highly prevalent in children worldwide and has been linked to various adverse health outcomes including rickets, osteomalacia, osteomalacic myopathy, sarcopenia, and weakness, growth retardation, hypocalcemia, seizure and tetany, autism, cardiovascular diseases, diabetes mellitus, cancers (prostate, colon, breast), infectious diseases (viral, tuberculosis), and autoimmune diseases, such as multiple sclerosis and Hashimoto's thyroiditis. Risk factors for hypovitaminosis D are people with darker skin pigmentation, use of sunscreen, insufficient ultraviolet B exposure, prematurity, living in northern latitudes, malnutrition, obesity, exclusive breastfeeding, low maternal vitamin D level, certain medications, drinking unfortified cow's milk, liver failure, chronic renal insufficiency, cystic fibrosis, asthma, and sickle cell hemoglobinopathy. This review highlights and summarizes the molecular perspectives of vitamin D deficiency and its potential adverse health outcomes in pediatric age groups. The recommended treatment regimen is beyond the scope of this review.